Examining the impact of rhythmic breathing and progressive muscle relaxation on acute pain following inguinal hernia repair: a parallel randomized clinical trial - Hosein Bagheri; Mobin Mottahedi; Seyedeh Solmaz Talebi; Sara Mehralizade; Hossein Ebrahimi (BMC Complementary Medicine and Therapies)
Abstract Background Acute postoperative pain is often reported after repair of inguinal hernia and can negatively impact patient satisfaction and clinical outcomes. This includes delayed wound healing, longer hospitalization, and increased health care costs. Non-pharmacological techniques like Progressive Muscle Relaxation (PMR) and Rhythmic Breathing (RB) have been suggested as possible interventions for managing this type of pain. The purpose of this study was to examine the effects of PMR and RB on postoperative pain following repair of inguinal hernia. Methods This parallel randomized controlled trial was conducted to examine 120 patients in the age range of 18 to 75 years with inclusion criteria: Repair of Inguinal Hernia under general anesthesia and no addiction to drugs and narcotics. These patients were randomly assigned to one of three groups: the RB group, PMR group, or the control group (which received standard care). The RB and PMR interventions were administered at 3, 6, 12, and 24 h after surgery. The primary outcome measure was the intensity of pain at the surgical site, assessed using the Visual Analog Scale (VAS). The secondary outcome measure was the amount of rescue analgesic (Pethidine). The one-way analysis of variance, Chi-square, post-hoc test, and repeated measures ANOVA were used for data analysis. Results Following the interventions, participants in both the RB and PMR groups exhibited significantly lower levels of acute pain after inguinal hernia repair compared to the control group across all four time periods, except at 12 h postoperatively in the RB group. However, there was no statistically significant difference between the RB and PMR groups. Additionally, the amount of pethidine consumed in the control group was significantly higher compared to the two experimental groups. Conclusions Based on the results, both RB and PMR were found to be effective techniques in reducing patients’ pain. Therefore, it is recommended that healthcare team members, particularly nurses, actively learn and teach both RB and PMR. Trial registration Registered in the Iranian registry of clinical trials ( www.irct.ir ) in 31/01/2023 with the following code: IRCT20200206046395N2.